Pemanfaatan Teledentistry Untuk Deteksi Karies Gigi Di Masa Pandemi COVID-19: A Scoping Review - Tiara Chairunissa, Risya; Erri Astoeti, Tri; Cloudya Panjaitan, Caesary (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: In 2018, Indonesian Baseline Health Research stated that the prevalence of dental caries in Indonesia is 88.8%, which indicates that it has the highest prevalence of oral and dental health issues in Indonesia If left untreated dental caries can cause issues that negatively affect someone’s quality of life. Throughout the COVID-19 pandemic, dentist appointments have been on a decline, due to fear of contracting COVID-19. Furthermore, PDGI have released a circular letter that urges direct dentist practice to be done only in emergency and advised dentists to give dental health service through teledentistry instead. This is supported by the regulation implemented by the Indonesian Medical Council and the Ministry of Health of the Republic of Indonesia regarding the use of telemedicine. Objective: The purpose of this research is to determine if the usage of teledentistry is effective in screening dental caries. Methods: The Scoping Review method on this research is systematically done in accordance with the PRISMA guidelines and uses the data basis of Google Scholar. Result: There are six journals included on this research, and each of them studied the use of teledentistry to screen dental caries. Conclusion: The research found that during the COVID-19 pandemic, early examination can be done with teledentistry which is proven effective in screening dental caries before patients are given further treatment by dentists, despite the limitations.